The political culture of the urban working classes in Costa Rica: the case of carpenters and cabinetmakers (1890-1943) - Rojas Sandoval, Francisco Javier (2002)
This article analyses the political culture developed by carpenters and cabinetmakers between the end of the nineteenth century and the year of promulgation of the Labour Code; in that sense it is intended to be a contribution to the analysis of the political culture developed by the urban working classes of Costa Rica.